Integrating the Cloud-Scenarios and Solutions - SHANKARARAMAN, Venky (Institutional Knowledge at Singapore Management University, 2012)
Cloud computing adoption is on the rise due to reduced infrastructure resources and a need for agility in meeting IT demands. However, many organizations will still have on-premise applications along side with applications in the cloud, and will have to deal with the challenges that arise from integrating all these applications. In this chapter, the authors briefly introduce the various cloud computing architecture layers, provide detailed cloud integration scenarios, and discuss some of the challenges and present some integration solutions. They also provide points for consideration to help organizations decide appropriate integration solutions to suit their needs.